2015
DOI: 10.1103/physrevb.92.041108
|View full text |Cite
|
Sign up to set email alerts
|

Route to room-temperature ferromagnetic ultrathinSrRuO3films

Abstract: Experimental efforts to stabilize ferromagnetism in ultrathin films of transition metal oxides have so far failed, despite expectations based on density functional theory (DFT) and DFT+U. Here, we investigate one of the most promising materials, SrRuO3, and include correlation effects beyond DFT by means of dynamical mean field theory. In agreement with experiment we find an intrinsic thickness limitation for metallic ferromagnetism in SrRuO3 thin films. Indeed, we demonstrate that the realization of ultrathin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 60 publications
5
49
1
Order By: Relevance
“…Specifically, for the N Ru = 4 case, the SrO‐terminated sample remains metallic, while the RuO 2 ‐terminated sample becomes highly insulating below 152 K. The N Ru = 3 film with RuO 2 ‐termination exhibits insulating behavior over the entire T range and a negligible FM signal. This behavior further implies that the RuO 2 ‐termination may facilitate an AF insulating phase …”
mentioning
confidence: 92%
“…Specifically, for the N Ru = 4 case, the SrO‐terminated sample remains metallic, while the RuO 2 ‐terminated sample becomes highly insulating below 152 K. The N Ru = 3 film with RuO 2 ‐termination exhibits insulating behavior over the entire T range and a negligible FM signal. This behavior further implies that the RuO 2 ‐termination may facilitate an AF insulating phase …”
mentioning
confidence: 92%
“…For the bulk phase, LDA, LDA+U , and self-interaction correction (SIC) give the correct ferromagnetic solution although the calculated moment shows some deviations [17,[50][51][52]. For the thin film SRO113, however, the experimentally observed metal-to-insulator transition (MIT) and the ferromagnetic-to-nonmagnetic transition as a function of layer thickness are not consistently reproduced by these techniques [16,[53][54][55][56][57]. For example, the singlelayer SRO113 is predicted to be either ferromagnetic or nonmagnetic depending on the choice of the exchangecorrelation functional and the U values [53,[55][56][57].…”
Section: Introductionmentioning
confidence: 97%
“…Although U is not sufficiently large to induce the Mott insulating state, Δ and J can hinder the intersite and intrasite orbital hybridizations, which produces a hard gap in the minor t 2g band. However, the effect of Δ on the anomalous orbital ordering is not obvious (i.e., the in-plane compressive strain may or may not simply increase the energy of the major d xy band), and different authors have proposed different views (e.g., refer to Gu et al, 2012;Gupta et al, 2014;Si et al, 2015). In addition, the authors of some reports argue that electronphonon coupling is an important factor.…”
Section: Final Remarksmentioning
confidence: 99%
“…Because of the Hubbard repulsion and enhanced localization of orbitals, the loss of symmetry induced by Δ produces a prominent effective splitting Δ eff (Poteryaev et al, 2007(Poteryaev et al, , 2008. A DFT+DMFT study has shown the antiferromagnetic and insulating STO/SRO/STO with one-unit-cell thickness (Si et al, 2015), with a decent Δ eff between d xy and d xz,yz .…”
Section: Hund's Couplingmentioning
confidence: 99%